2022
DOI: 10.3390/biom12121869
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis for Altering Side Chain Length on Cannabinoid Molecules and Their Effects in Chemotherapy and Chemotherapeutic Induced Neuropathic Pain

Abstract: (1) Background: Recently, a number of side chain length variants for tetrahydrocannabinol and cannabidiol have been identified in cannabis; however, the precursor to these molecules would be based upon cannabigerol (CBG). Because CBG, and its side chain variants, are rapidly converted to other cannabinoids in the plant, there are typically only small amounts in plant extracts, thus prohibiting investigations related to CBG and CBG variant therapeutic effects. (2) Methods: To overcome this, we developed an effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Mechanical sensitivity measurements were taken before the beginning of cisplatin administration and after four weeks of cisplatin, termed "Baseline" and "Neuropathy", respectively. Measurements were performed by using an electronic von Frey anesthesiometer (IITC Life Sciences Inc., Woodland Hills, CA, USA) exactly as previously described [10,11,14,22,38]. The experimenter performing von Frey was blinded to all treatment groups.…”
Section: Measurement Of Mechanical Hypersensitivity-von Freymentioning
confidence: 99%
“…Mechanical sensitivity measurements were taken before the beginning of cisplatin administration and after four weeks of cisplatin, termed "Baseline" and "Neuropathy", respectively. Measurements were performed by using an electronic von Frey anesthesiometer (IITC Life Sciences Inc., Woodland Hills, CA, USA) exactly as previously described [10,11,14,22,38]. The experimenter performing von Frey was blinded to all treatment groups.…”
Section: Measurement Of Mechanical Hypersensitivity-von Freymentioning
confidence: 99%
“…This suggests that CBC may possess broad pain-relieving properties, which are unique among minor cannabinoids. For example, previously, we found that another minor cannabinoid, CBG, was effective at reducing neuropathic pain in male and female mice, but less effective at reducing pain in the formalin and tail-flick assays [17,42]. Additionally, in a previous study, we found that CBD's antinociceptive effect occurred only during the acute phase of the formalin assay in male mice (not in female mice) and that CBD was not effective at reducing mechanical hypersensitivity in a mouse model of chemotherapy-induced peripheral neuropathy (CIPN) [15,18].…”
Section: Discussionmentioning
confidence: 95%
“…Evidence suggests that THC, CBD, and CBG are effective antinociceptive agents with binding affinities for many receptors involved in pain modulation [5][6][7][8][9][10][11][12][13]15,17,18,42]. Given that CBC is derived from the same plant and possesses a significant positive correlation in its binding profile compared to other phytocannabinoids (Figure 1A), we next investigated whether CBC had binding affinity for receptors known to play a role in pain modulation.…”
Section: Cbc's Receptor Binding Profile In Comparison To Other Phytoc...mentioning
confidence: 99%
“…Briefly, the required CBD variants of differing sidechain lengths can be synthesized by reacting a stereospecific menthadienol isomer with resorcinol molecules of the desired sidechain lengths [18,22]. As recently described, such resorcinol molecules can be efficiently synthesized by Wittig reaction of 3,5-dimethoxylbenzyl triphenylphosphonium bromide with aldehydes corresponding to the desired sidechain lengths, followed by Pd/C-catalyzed hydrogenation, then deprotection and hydrolysis of aryl methyl ether groups to hydroxyl groups by reaction with BBr3 [22]. Additionally, hydrogenation of Δ 8 -and Δ 9 -THCP forms the analogue HHCP [19].…”
Section: Cbd-derived Cannabinoidsmentioning
confidence: 99%